LOYALITAS PENDENGARAN RADIO DI MASA PANDEMI COVID-19 - Arintya gantini Putri (JURNAL PURNAMA BERAZAM, 2022)
Competition of conventional media such as Radio with Online media is very tight. Listeners' loyalty is the main factor of radio as a conventional media to survive. Loyalty is a behavioral response as a form of commitment and satisfaction of a person towards a particular brand, which is a function of the psychological process. Such is the case with radio broadcasting stations. The better the quality of service, the higher the loyalty of radio listeners, and vice versa. Every year the number of listeners of Radio Dahlia 101.5 FM Bandung has successfully increased, this proves that the loyalty of radio listeners and the interest of the public to listen to the radio are increasing every year, due to the quality of programs and individual approaches of broadcasters with listeners as well as management with listeners. Especially in the COVID - 19 pandemic, the role of mass communication is very important and the loyalty of radio listeners shows an increase due to behavioral factors during the pandemic also influential.